Permanent storage of carbon dioxide in mafic rock formations: exploring Sweden’s potential - Crafoord, Emelie; Wanhainen, Christina; Bark, Glenn (Frontiers in Climate, 2025)
Mineral carbonation in reactive bedrock offers a rapid and permanent method for carbon dioxide (CO2) sequestration, converting CO2 into stable mineral phases within a geologically short timeframe. This study presents the first-ever systematic assessment of onshore CO2 mineral storage potential in Sweden, based on fieldwork, sampling, and mineralogical and geochemical analyses conducted at 23 localities. While this theoretical assessment cannot resolve uncertainties related to reactivity, dissolution capacity, and sequestration efficiency, it provides a critical foundation for identifying potentially favorable storage reservoirs. The findings highlight the Örnsköldsvik and Sundsvall areas in central Sweden, hosting a gabbro-anorthosite complex together with a set of dolerites, as the more suitable lithologies for onshore CO2 storage. These rocks are distinguished by their high content of reactive minerals—including olivine, Ca-rich plagioclase, and clinopyroxene—and low content of alteration phases. In the few locations where secondary phases such as serpentine and chlorite were observed, they were confined to grain boundaries and microfractures and did not appear to be pervasive throughout the rock. This preservation of primary mineralogy and textures supports the interpretation that these two lithologies are among the most suitable for CO2 mineral storage within the studied rock formations, under geochemical and thermal conditions favorable for mineral carbonation. This work provides the necessary foundation for future and ongoing experimental validation of reactivity and permeability and detailed site-specific investigations.